Energy of Learning from Home: The Power of Parental Involvement in The Academic Achievement of Indonesian Teens - Sasqia Desta Safitri; Subaidi subaidi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The process of adolescent development, education is an important thing that needs to be considered by parents. The attention given by parents is considered to support adolescent academic achievement. This study aims to determine the effect of parental involvement in education on adolescent academic achievement. The population of this study was high school students in Bandar Lampung City with a total of 351 respondents. This study is a descriptive quantitative study with a simple regression analysis technique using JASP 0.19.3.0 data analysis software. The scales used in this study include an academic achievement scale with a reliability of 0.848 and a parental involvement scale with a reliability of 0.957. The scales were distributed online via Google Forms. The results showed a coefficient of determination (R2) of 0.451 with (p <0.001) which means there is a significant relationship between parental involvement and academic achievement. The parental involvement variable provides an effective contribution of 45.1% and the hypothesis in this study is accepted.